A review of bacteriological profile of acute pyogenic meningitis in a tertiary care center in Southwest Nigeria - Joseph, Adejoke Adijat; Alao, Michael Abel; Oladipo, Tunde; Taiwo, Samuel Sunday; Popoola, Gbenga Olutade; Joseph, Oluyemi Adesoji (Journal of Surgery and Medicine, 2019)
Aim: Pyogenic meningitis remain a major cause of mortality and morbidity in lower middle income countries. There exists a wide variability in antibiogram profile of infective causes of acute pyogenic meningitis seeking for individualized management protocol. This study aim to review a five years profile of isolates from suspected cases and evaluate the antibiogram of the infective agent in a tertiary hospital in South west Nigeria. Methods: All patients presenting to the hospital with signs and symptoms suggestive of meningitis were evaluated. Aside random plasma glucose, CSF samples were sent for biochemistry, gene expert for tuberculosis and cultured on Blood agar, Chocolate agar and MacConkey agar for neonates and read after 24hours incubation. Results: 393 of the 657,890 patients seen in the hospital over a five year period suspected to have meningitis were investigated, 22(7%) had a positive culture. Streptococcus pneumoniae (31.8%), Haemophilus influenzae (27.4%), other Enterobacteriaceae (18.2%), Pseudomonas aeruginosa (9.1%), Staphylococcus aureus (4.5%), Proteus mirabilis (4.5%) and Candida albicans (4.5%) were isolated. Conclusion: Spectrum of causative bacterial agent is not different from documented in other parts of the country. Streptococcus pneumoniae predominance was reported which is sensitive to Ampicillin, Ceftriaxone, Cefotaxime and Penicillin. Empirical treatment with Ceftriaxone or Cefotaxime can be instituted while awaiting laboratory confirmation in suspected cases.